Plasma disposition kinetics of albendazole and its metabolities in laying hens - Bistoletti, Mariana (2009)
Endoparasites are a common and frequently underestimated problem, in avian production systems. Flubendazole is the only benzimidazole (BZD) anthelmintic licensed for use in poultry. However, other BZD drugs such as albendazole (ABZ) are “extra-labeled” used in poultry. The available information on BZD pharmacokinetic (PK) properties in poultry is scarce. The aim of the current work was to evaluate the plasma disposition kinetics of ABZ and its sulphoxide (ABZSO) and sulphone (ABZSO2) metabolites after intravenous (iv) administration to laying hens. Six (6) hens were iv treated with ABZ (10 mg/kg). Blood samples were taken up to 72 h post-treatment and plasma analyzed by HPLC. ABZ showed an initial concentration (C0) of 15.2 μg/mL, which rapidly decreased until the lowest concentration (0.107 μg/mL) attained at 12 h postadministration. The ABZ AUC value was 10.2 μg.h/mL and T½el was 3.85 h. ABZSO and ABZSO2 reached peak concentration of 3.21 and 0.34 μg/mL, respectively. ABZSO and ABZSO2 plasma concentration profiles were higher than those of ABZ parent drug, with AUC values of 26.3 μg.h/mL (ABZSO) and 15.6 μg.h/mL (ABZSO2). The work contributes with basic PK information useful to assess the potential therapeutic use of ABZ in laying hens.